Acute Abdomen: An Enigma - Rawal, Sushil; Shrestha, Dhan Bahadur; Thapa, Bikash Bikram; Shah, Kunda Bikram; Jha, Manoj (Nepalese Medical Journal, 2018)
Mesenteric infarction is a surgical emergency presenting as acute abdomen. Here we present a case of unexpected diagnosis of acute mesenteric infarction. He underwent emergency laparotomy with resection of the gangrenous bowel and end- end anastomosis of remaining 140 cm small bowel left. In two weeks period patient develop recurrence of disease which was successfully managed with conservative treatment. Further detailed investigation revealed the bizarre arterial anatomy with occlusion at multiple sites. Nepalese Medical Journal, vol.1, No. 1, 2018, Page: 48-50